Synthesis of Tungsten Oxide Nanorods by the Controlling Precipitation Reaction: Application for Hydrogen Evolution Reaction on a WO3 Nanorods/Carbon Nanotubes Composite Film Modified Electrode. Issue 4 (3rd January 2013) - Chekin, Fereshteh; Bagheri, Samira; Bee Abd Hamid, Sharifah
Abstract Tungsten trioxide nanorods (WO3) were prepared by controlling the precipitation reaction of sodium tungstate dehydrates solution and hydrothermal process. The synthesized tungsten trioxide nanorods have been characterized by X‐ray diffraction (XRD), energy dispersive spectroscopy (EDS), scanning electron microscopy (SEM), cyclic voltammetry (CV) and linear sweep voltammetry (LSV). Electrochemical activity for hydrogen evolution reaction (HER) on WO3 nanorods / carbon nanotube (WO3/CNT) composite electrocatalyst was first studied in acid solution (0.1 M H2SO4) at room temperature. The overall experimental results revealed that the electrocatalytic activity for HER on WO3/CNT is two order magnitude higher than those obtained with WO3 nanorods and is four times than in the case of commercial WO3 in 0.1 M H2SO4. On the other hand, the kinetic reaction mechanisms were discussed on WO3/CNT electrocatalysts in acid solution for HER. However, the rate‐determining step carries through Tafel reaction on commercial WO3, CNT, WO3 nanorods and WO3/CNT electrocatalysts in acidic solution was introduced.